2019
DOI: 10.1007/s42452-019-0925-2
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation and parameter analysis of LPG refrigeration system using Taguchi method

Abstract: In this research work, an attempt has been made to study the liquefied petroleum gas (LPG) as an alternative refrigerant to eliminate the global warming potential causes many dangerous impacts on the environment by conventional refrigerants. An LPG refrigeration experimental setup has been fabricated using different lengths of capillary tubes, pressure regulator, evaporator, LPG supply unit, and gas burner. Initially, the parameters working ranges have been confirmed by conducting Exploratory experiments. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…The levels of each process variable are arranged in Table 1. The experimentations are steered using the L9 orthogonal array of the Taguchi method [10] and the MRR and Ra values observed over the trials are shown in Table 2.…”
Section: Experimental Setup and Experimentationmentioning
confidence: 99%
“…The levels of each process variable are arranged in Table 1. The experimentations are steered using the L9 orthogonal array of the Taguchi method [10] and the MRR and Ra values observed over the trials are shown in Table 2.…”
Section: Experimental Setup and Experimentationmentioning
confidence: 99%
“…The levels of each process variable are tabulated in Table 1. The near-dry WEDM experiments are conducted [18], and the MRR and WWR values observed through the experiments are shown in Table 2. 2.…”
Section: Wwrmentioning
confidence: 99%
“…Control parameters and their levels for the Taguchi design are selected and shown in Table 1. The orthogonal array L9 and L27 are suitable for three levels of three parameters Taguchi analysis (Boopathi, 2019;Boopathi et al, 2012;Boopathi & Myilsamy, 2021;Boopathi & Sivakumar, 2013, 2014. In this study, the L27 orthogonal array has been selected and the Mean value of three replication of testing are observed in the Table 2.…”
Section: Experimental Setup and Proceduresmentioning
confidence: 99%
“…The mean hardness and permeability values (raw data) are considered to find the best level of the control parameters by Taguchi analysis (Boopathi & Sivakumar, 2013;. The maximization of permeability is taken as Larger as better and average hardness is expected as nominal as better (Boopathi, 2019). The analysis of variation test was performed for both responses.…”
Section: Taguchi Analysismentioning
confidence: 99%